2021
DOI: 10.1016/j.heliyon.2021.e07009
|View full text |Cite
|
Sign up to set email alerts
|

The impact of the city skyline on pleasantness; state of the art and a case study

Abstract: The research deals with the effect of skylines on citizens' pleasantness. The research method is based on the respondents' judgment of the color images of the skylines. 360 citizens were asked to complete a questionnaire to express their opinions and preferences along with the reasons. Three types of nature, traditional, and contemporary skylines were identified as the dominant skylines. The results showed that people prefer the nature and the traditional skyline over the contemporary skyline. They introduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The current construction of new cities seeks speed and quantity and does not invest enough in shaping the spatial hierarchy, resulting in a new city skyline with a single hierarchy, lacking rhythm and cultural connotation, and disconnected from the old city and the natural environment. A city's unique skyline can serve as a representative image of the city, and in the above context, the study of the city skyline has strong practical significance [19]. Puspitasari A W et al obtained that linear clusters have higher visibility by comparing different layouts of circular, rectangular, and linear geographic area organisations in high-rise complexes [20].…”
Section: Of 19mentioning
confidence: 99%
See 1 more Smart Citation
“…The current construction of new cities seeks speed and quantity and does not invest enough in shaping the spatial hierarchy, resulting in a new city skyline with a single hierarchy, lacking rhythm and cultural connotation, and disconnected from the old city and the natural environment. A city's unique skyline can serve as a representative image of the city, and in the above context, the study of the city skyline has strong practical significance [19]. Puspitasari A W et al obtained that linear clusters have higher visibility by comparing different layouts of circular, rectangular, and linear geographic area organisations in high-rise complexes [20].…”
Section: Of 19mentioning
confidence: 99%
“…Puspitasari A W et al obtained that linear clusters have higher visibility by comparing different layouts of circular, rectangular, and linear geographic area organisations in high-rise complexes [20]. Mehrdad Karimimoshaver et al used respondents' judgments of colour images of the skyline on the three types of natural, traditional, and modern skylines and obtained that people preferred natural and traditional skylines [19]. Caner Guney et al considered Istanbul's skyline as a unique asset, and to maintain the original architectural composition of the skyline and to study the aesthetics of the city's skyline and its change as a result of tall structures, a study was conducted by using a GIS system for transformations that occur; this is achieved by customising the geographic model in a GIS environment [13].…”
Section: Of 19mentioning
confidence: 99%
“…With respect to quantitative definitions, some progress was made since [59]. Several studies concentrate on one specific landscape element, e.g., walking path geometry [27] (having found that people tend to prefer curvy paths), oppressiveness due to building height [40], skyline impression [60], visual quality of urban water landscapes [61,62], and building exteriors [63]. Combined approaches include mostly landscape aesthetics indicators, e.g., [29], who developed beauty indexes and also distinguished landscape type; the morphologic scenic beauty estimation model of [64]; an aesthetic assessment approach [65]; and modelling of the aesthetics of urban-rural fringes [66].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Of course, vegetation proportion and sky proportion cannot explain all the variations of visual effect scores. This means that, apart from the two main factors, the visual effect contains some more complex factors, such as the rhythm of the skyline [27,28], the color and style of buildings [29], and so on. With the Elo rating method, more detailed research on different factors of visual effect could be quantitatively discussed in the future.…”
Section: Effect Of Typical Landscape Proportions In the Pictures To V...mentioning
confidence: 99%